Construction of cloning, promoter-screening, and terminator-screening shuttle vectors for Bacillus subtilis and Streptococcus lactis. - van der Vossen, J M (1985)
Shuttle vectors have been constructed which are suitable both for the selection of regulatory sequences and for gene cloning in Bacillus subtilis and Streptococcus lactis. The promoter screening vectors contain a promoterless chloramphenicol acetyltransferase gene; the insertion of suitable DNA fragments upstream of the gene restored the enzyme activity. With a related set of vectors, transcription termination signals can be selected.